Relative Tissue Oxygenation and Temperature Changes for Detecting Early Upper Extremity Skin Ischemia. Issue 4 (October 2019) - Polfer, Elizabeth M.; Sabino, Jennifer M.; Fleming, Isaac C.; Means, Kenneth R.
Abstract : Summary: The authors' purpose was to determine whether there are reliable noninvasive methods of assessing upper extremity ischemia regardless of skin pigmentation. The authors conducted a study of healthy subjects classified based on skin pigmentation using the Fitzpatrick scale, the von Luschan color scale, and self-described race (two Hispanics, three Caucasians, and four African Americans). A surface temperature probe and a near-infrared spectroscopy monitor were placed on the posterior interosseous artery skin territory. Temporary upper limb ischemia was induced by tourniquet insufflation. Readings from both devices were taken at baseline and every 15 seconds for a total of 10 minutes of ischemia. During tourniquet insufflation, the authors found a reliable decrease in tissue oxygenation measured by near-infrared spectroscopy in all subjects and no significant change in temperature readings for any subjects. There was an average decrease of 19 percent in tissue oxygenation using near-infrared spectroscopy, with measurements on average starting at 77 percent and ending at 57 percent. There was no significant difference in the change in near-infrared spectroscopy oxygenation between participants with Fitzpatrick skin types 3, 4, and 5 or when participants were grouped into Fitzpatrick skin type less than or equal to 3 versus greater than 3, or when grouped into Fitzpatrick skin type less than or equal to 4 versus greater than 4. There was also no significant difference in participants grouped into von Luschan scores less than or equal to 20 versus greater than 20. In this healthy subjects study, near-infrared spectroscopy rapidly identified ischemia in all cases, whereas skin surface temperature did not. Near-infrared spectroscopy may be a reliable way of noninvasively monitoring for ischemia regardless of skin pigmentation degree. CLINICAL QUESTION/LEVEL OF EVIDENCE: Diagnostic, IV.